Current reforms in teacher education occurring in France and the United States: placing socio-historical elements in perspective, starting with the concept of education - Lenoir, Yves (Swiss Journal of Educational Research, 2002)
Supported by a socio-historical perspective, the purpose of this article is to highlight the existing leading characteristics in the conception of actualized modalities of the teacher education systems in France and the United States. These dominant conceptions emerge from two traditions initiated in their respective educational systems. Both traditions have a common foundation in the emancipation of human beings, directly linked to the function of a modern nation-state school system and created from distinct socio-historical dynamics, and are actualized differently in their respective society. In the context of current international exchange, characterized by, among other things, a neoliberal hegemonistic ideology, an approach used by a diversity of organizations and supported by the North American influence, the introduction of these elements of the North American argument into the French educational system could be the source of important disequilibrium, thus disrupting its current perspective and provoking ruptures in the current internal coherence of the European French speaking educational system.